Prohibition on Social Business Transaction Practices of E-Commerce Tiktok Shop Based on The Minister of Trade Regulation No. 31 of 2023 - Ainun Adilla Siregar; Edy Ikhsan; Mahmul Siregar (Universitas Efarina, 2025)
The main concept in the development of social commerce based on the Regulation of the Minister of Trade of the Republic of Indonesia Number 31 of 2023 concerning Business Licensing, Advertising, Guidance, and Supervision of Business Actors in Trading Through Electronic Systems based on article 21 number 3 is that Electronic Trading Organizers (PPMSE) with a Social Commerce business model are prohibited from Facilitating Payment Transactions on their Electronic Systems. The prohibition on social commerce that carries out online transactions at the same time on one platform in Indonesia is related to efforts to prevent potential monopolies. There should not be two shopping functions on one platform with social media, this must be separated because this is related to licensing and supervision issues. The prohibition on direct transactions on social commerce aims to prevent control of algorithms to protect personal data from business interests. All platforms that provide direct transactions are prohibited because they can create unfair business competition, especially the TikTok Shop platform can use user information to control the algorithm on TikTok Shop, user data without permission is used for marketing and sales purposes, this can lead to market control and result in potential monopolistic practices. The research that has been conducted is a normative legal research that focuses on norms and legal objects as the main data. The results of this study are: (1) the Ministry of Trade issued strict regulations to TikTok in the Regulation of the Ministry of Trade Number 31 of 2023 in Article 21 Paragraph 3 that PPMSE with a social-commerce business model, namely social media organizers, are prohibited from facilitating payment transactions on electronic systems. TikTok only has a license as a social media, not as a market place, so social media and market place must be separated. (2) The prohibition on combining e-commerce with social media in the same application is regulated in the Regulation of the Minister of Trade Number 31 of 2023 in Article 21 Paragraph (3) that PPMSE with a social-commerce business model, namely social media organizers, are prohibited from facilitating payment transactions on electronic systems. In this regulation, social commerce must first obtain a permit before being able to operate in Indonesia. This regulation prohibits social media and social commerce from facilitating transactions and payments like e-commerce. Social commerce is only allowed for promotion or advertising without transactions. (3) The results of the analysis with the emergence of legal uncertainty in the Tiktok Shop incident which combines social commerce and e-commerce in one social media platform are, First, the business operations carried out by Tiktokshop are contrary to the Regulation of the Minister of Trade Number 31 of 2023, which prohibits the combination of social commerce with e-commerce. Second,there are no significant changes to the previous TiktokShop with the current Tiktokshop, such as social e-commerce transactions which are still carried out on the Tiktok social media application itself. Third, there are indications of legal uncertainty. The government at one time prohibited the Tiktokshop business practice for various considerations, but in a short time later allowed the business practice again using the same legal regulations as the regulations to prohibit the Tiktokshop business practice.